Improving Coherence of The Students’ Sentences by Applying Thematic Progression And Personal Blog In The Sentence-Based Writing Class - Adi Purnomo (IAIN Salatiga, 2014)
This study was aimed at describing what kinds of thematic progressionpatterns mostly employed by the students, describing how to applythematic progression theory and personal blog in the sentence-basedwriting class, and finding out whether the use of thematic progressiontheory and personal blog give positive significances to coherence of thestudents‘ sentences. This is an action research study employing twocycles. The subject of the study was 24 students of group 2, in a class ofsentence-based writing (SBW), and the object of the study was students‘sentences created by the students in the teaching and learning process(TLP). The result of the study shows that thematic progression patternsmoslty employed by the students are constant theme pattern followed byzig zag and multiple theme patterns. In TLP, the materials were devidedand given to the students in two cycles. The first cycle focused onintroducing the thematic progression theory and its kinds of patterns.Then, in the next cycle the students focused on sharing ideas with otherclassmates via individual blogs. Based on the result of the study, teachingSBW using thematic progression theory gives its positive significance byvaried patterns used by the students. It can be seen from the analysis ofthe students‘ sentences from pretest, paragraf 1, paragraf 2, paragraf 3and posttest. The students also give positive responses upon its teaching and learning process using thematic progression and personal blogs basedon the pre and post test questionnaire data. It is hoped that the result ofthe study gives positive contribution to the students in preparing them towrite in bigger contexts - paragraph-based writing, genre-based writngand academic writing in the next coming semesters.Keywords: Mind mapping ; writing skills ; Class Action Research.